2011
DOI: 10.1088/0004-637x/739/1/44
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Optics Imaging of Quasi-Stellar Objects With Double-Peaked Narrow Lines: Are They Dual Active Galactic Nuclei?

Abstract: Active galaxies hosting two accreting and merging super-massive black holes (SMBHs) -dual Active Galactic Nuclei (AGN) -are predicted by many current and popular models of black hole-galaxy coevolution. We present here the results of a program that has identified a set of probable dual AGN candidates based on near Infra-red (NIR) Laser Guide-Star Adaptive Optics (LGS AO) imaging with the Keck II telescope. These candidates are selected from a complete sample of radio-quiet Quasistellar Objects (QSOs) drawn fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 42 publications
3
75
0
Order By: Relevance
“…Nevertheless, our followup observations (Liu et al 2010a;Shen et al 2011a) of a subset of a systematically selected sample of 167 AGNs with double-peaked NELs (Liu et al 2010b; see also Smith et al 2010;Wang et al 2009), as well as studies by other groups Fu et al 2012), have demonstrated the feasibility and importance of combining higher resolution NIR imaging (Fu et al 2011a;Rosario et al 2011) and spatially resolved optical spectroscopy (Comerford et al 2012) to discriminate kpcscale binary AGNs from single-AGN-NLR gas kinematics. Kpc-scale binary AGNs tend to show two concentrated [O III] nuclei spatially coincident with two stellar bulges in a merger, with the dynamics dominated by the potential of the individual stellar bulges.…”
Section: Systematic Searches For Kpc-scale Binary Agnsmentioning
confidence: 81%
See 1 more Smart Citation
“…Nevertheless, our followup observations (Liu et al 2010a;Shen et al 2011a) of a subset of a systematically selected sample of 167 AGNs with double-peaked NELs (Liu et al 2010b; see also Smith et al 2010;Wang et al 2009), as well as studies by other groups Fu et al 2012), have demonstrated the feasibility and importance of combining higher resolution NIR imaging (Fu et al 2011a;Rosario et al 2011) and spatially resolved optical spectroscopy (Comerford et al 2012) to discriminate kpcscale binary AGNs from single-AGN-NLR gas kinematics. Kpc-scale binary AGNs tend to show two concentrated [O III] nuclei spatially coincident with two stellar bulges in a merger, with the dynamics dominated by the potential of the individual stellar bulges.…”
Section: Systematic Searches For Kpc-scale Binary Agnsmentioning
confidence: 81%
“…Shen et al (2011a) combined high-resolution NIR imaging (to resolve the double stellar bulges and to detect tidal features) with spatially resolved optical spectroscopy (to locate the ionizing sources and to register with the BHs/bulges) to identify strong kpc-scale binary-AGN candidates (see also McGurk et al 2011). Detecting two stellar components alone (e.g., Fu et al 2011a;Rosario et al 2011) is not a sufficient condition for identifying binary AGNs, as the double-peaked profile could be caused by NLR gas kinematics around a single AGN in a merger. Neither is detecting spatial offsets between the emission-line components alone (e.g., Gerke et al 2007;Comerford et al 2009a;Barrows et al 2012) a sufficient condition, even though most double-peaked AGNs show spatial offsets on kpc scales between the two velocity components (Shen et al 2011a;Fu et al 2012;Comerford et al 2012), because such spatial offsets are also expected and commonly observed in single AGNs due to the spatial extent of the NLR, as demonstrated by Fischer et al (2011) in Mrk 78 (see also Whittle & Wilson 2004).…”
Section: X-ray Confirmation Of Optical Candidates: Success and Ambiguitymentioning
confidence: 99%
“…Follow-up adaptive optics (AO) imaging strived to resolve smaller-separation stellar components in 55 galaxies with double-peaked [O iii] λ5007 (Fu et al 2011a;Rosario et al 2011;Fu et al 2012). In addition to obtaining integral field unit (IFU) spectroscopy of 42 galaxies with double-peaked [O iii] λ5007, Fu et al (2012) also analyzed high-resolution Advanced Camera for Surveys/WFC2 archival Hubble Space Telescope (HST) images of six additional double-peaked galaxies.…”
Section: Multiwavelength Observations From the Literaturementioning
confidence: 99%
“…Although position angles between the stellar components are not reported in the literature (Fu et al 2011a;Rosario et al 2011;Fu et al 2012), we estimate the position angles for these seven objects based on our best estimates of the bright centroid of each component in the published images. In Section 7.4.2, we compare these position angle estimates, as well as the reported spatial separations, to the position angles and spatial separations measured from our long-slit spectroscopy.…”
Section: Multiwavelength Observations From the Literaturementioning
confidence: 99%
“…Such systems have so far, however, been identified in only a handful of sources (e.g., Deane et al 2014;Müller-Sánchez et al 2015). Radio sources that exhibit double peaks in their emission line spectra are good candidates for binary AGN (Liu et al 2010;Rosario et al 2011;Comerford et al 2013). As are sources exhibiting highly distorted jets and lobes, called X-shaped sources (Cheung 2007;Lal & Rao 2005, 2007.…”
Section: Introductionmentioning
confidence: 99%